Risk Factors for Obstructed Labour in Eastern Uganda: A case control study - Musaba, Milton W.; Ndeezi , Grace; Barageine, Justus K.; Nankabirwa, Victoria; Wandabwa, Julius N. (PloS one, 2020)
Obstructed labour (OL) is an important clinical and public health problem because of the associated maternal and perinatal morbidity and mortality. Risk factors for OL and its associated obstetric squeal are usually context specific. No epidemiological study has documented the risk factors for OL in Eastern Uganda. This study was conducted to identify the risk factors for OL in Mbale Hospital.